2000
DOI: 10.1029/1999jd900253
|View full text |Cite
|
Sign up to set email alerts
|

UV‐B irradiance at Madrid during 1996, 1997, and 1998

Abstract: Abstract. During 1996, 1997, and 1998, several total ozone depletion events were detected over Madrid (40øN, 3øW) in late spring and in winter. A broadband interferential filter instrument (UV-300) centered at 298 nm was used to monitor the solar UV-B irradiance on the ground, registering UV-B levels as high as 17.1 /xW/cm 2 (May 2, 1997, solar zenith angle SZA -35 ø, 03 = 268 Dobson units). The data obtained have been compared to that measured with two commercial biometers (PMA2102 and Solar Light 501A), show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Some studies analyze the influence of OMs on UV radiation at different countries in Centre and North Europe, such as United Kingdom [ Austin et al , 1999], Norway [ Orsolini et al , 2003], Czech Republic [ Schmalwieser et al , 2004], and Germany [ Stick et al , 2006]. However, very few results about the UV radiation variability attributed to OMs episodes have been published to date in Spain [ Córdoba et al , 2000]. These studies are of high interest in this country, and particularly in the southwestern due to the high UV radiation recorded at these latitudes throughout the year [ Serrano et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies analyze the influence of OMs on UV radiation at different countries in Centre and North Europe, such as United Kingdom [ Austin et al , 1999], Norway [ Orsolini et al , 2003], Czech Republic [ Schmalwieser et al , 2004], and Germany [ Stick et al , 2006]. However, very few results about the UV radiation variability attributed to OMs episodes have been published to date in Spain [ Córdoba et al , 2000]. These studies are of high interest in this country, and particularly in the southwestern due to the high UV radiation recorded at these latitudes throughout the year [ Serrano et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Very few results about UV radiation analyses during ozone mini-hole episodes have been published to date in Spain (Córdoba et al, 2000;Antón et al, 2007). These studies have a great interest in this country, and particularly in the Extremadura region (South-Western Spain) due to the high UV radiation values measured at these latitudes throughout Correspondence to: M. Antón (mananton@unex.es) the year (Serrano et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Siani and Galliani (2002) analysed an ozone minihole which appeared at the end of November 2000 in Central Europe by means of a model that forecasts the ozone concentration tendency. Relevant studies in Spain are by Córdoba et al (2000), Pérez et al (2002), Gil et al (2004) and Serrano et al (2006). Córdoba et al (2000) and Pérez et al (2002) studied mini-hole episodes in Madrid over a 3-year period, showing that the increase in solar radiation is more pronounced in the UVB range (280-315 nm) than in the UVER.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies in Spain are by Córdoba et al (2000), Pérez et al (2002), Gil et al (2004) and Serrano et al (2006). Córdoba et al (2000) and Pérez et al (2002) studied mini-hole episodes in Madrid over a 3-year period, showing that the increase in solar radiation is more pronounced in the UVB range (280-315 nm) than in the UVER. Gil et al (2004) showed that the historic minimum of the total ozone amount in the Iberian Peninsula occurred on 10 January, 2004.…”
Section: Introductionmentioning
confidence: 99%